Hyperflav — perspective photosensitizer for PDT: cell studies - Yermak, P.V.; Gamaleia, N.F.; Shalamay, A.S.; Saienko, T.V.; Kholin, V.V. (Experimental Oncology, 2010)
Present studies investigated the effectiveness in vitro of Hyperflav application as a photosensitizer for photodynamic therapy.